Future Buildings Standard : Consultation on changes to Part L (conservation of fuel and power) and Part F (ventilation) of the Building Regulations for non-domestic buildings and dwellings ; and overheating in new residential buildings.: Consultation on changes to Part L (conservation of fuel and power) and Part F (ventilation) of the Building Regulations for non-domestic buildings and dwellings ; and overheating in new residential buildings. (2021) - Unknown
No abstract available